Group portrait of the 1960 Monte Toyon meeting in Aptos, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of a Monte Toyon meeting, held July 31 to August 1, 1960 at Monte Toyon in Aptos, California.